PENGALAMAN VOLUNTOURISM BAGI VOLUNTOURIST DAN MASYARAKAT LOKAL DI YAYASAN SARI HATI, UBUD, GIANYAR, BALI - Yoga, Anak Agung Gde Rama Purwani; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 4 No 1 (2016): VOL 4, NO 1 (2016): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2016.v04.i01.p08, 2016)
Abstract This research located at Yayasan Sari Hati, Ubud that focus on voluntourism experience for the voluntourist and the local community. Voluntourism is a type of alternative tourism that can bring an unique and different experience not only for the voluntourist but also for the local community. Voluntourism experience considered as a cathartic experience that can make a positive difference for the voluntourist. The aim of this paper is to know the voluntourism experience that gained by the voluntourist and the local community also how that experience can make a difference for the voluntourist itself. Through participant observation, researcher participate actively in the voluntourism activity at Yayasan Sari Hati. Data also collected by literature review and indepth interview with two voluntourists and four local communities for then analyzed by qualitative technique. This paper reviews voluntourism experience for the voluntourist and the local community also the experience that make difference for the voluntourist. This paper concluded that voluntourism experience is a form of cathartic experience through tourism which is not only can bring a valuable knowledge for the voluntourist but also can change their personality and lifestyle.
Keywords: Voluntourism Experience, Voluntourist, Local Community